Some further results on ideal convergence in topological spaces - Das, Pratulananda (Topology and its applications, 2012)
In this paper we make some further investigations on ideal convergence and in particular we concentrate on I-limit points and I-cluster points. We try to establish the characterization of the set of I-limit points (which has not been done in any structure so far) and show that this set can be characterized as an Fσ-set for a large class of ideals, namely analytic P-ideals and then make certain interesting observations on I-cluster points.